PERKEMBANGAN PENDIDIKAN DI KABUPATEN NATUNA PASCA PEMEKARAN (2006-2013) - Halifah, Musdar Halifah Musdar; Saiman, Marwoto Saiman Marwoto; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : Natuna district education office has the arduous task in advancing education in the District Natuna after the split, after the division of the education department autonomously take care of the quality of education and the development of education in its own country, because after the expansion of education in the Natuna has not reached the desired target by the community and local government. Achievement of the National Examination in the 2010-2011 school year. Department of Education District Natuna need accurate measures and hard work. By carrying out the qualifications of teachers in the District Natuna and will provide tutoring outside of school to students.The purpose of the study was to (1) determine the expansion history of the area in Riau Islands District Natuna Regency, especially in the years 2006-2013. (2) determine the development of education in post-Proliferation Natuna Regency 2006-2013. (3) determine the barriers faced by the District Education Office Natuna 2006-2013.This type of research is descriptive qualitative approach that aims to provide a systematic overview of the state of the ongoing research on the object. Where research is Natuna. When the study is planned for 4 months. Data collection techniques in this study included three observation techniques, interviewing techniques and engineering documentation.Redistricting beginning in Natuna very poor education ranging from teaching staff, teaching and support facilities for student activities, I do not believe in early expansion of education Natuna Regency will get priority from the regional government, the local government today education in Natuna Regency is good in my opinion, the local government to fix Natuna education with a strong will, repair performed by the government ranging from Kesara faculty to support teaching and learning activities. Obstacles encountered in floating Education in Natuna Regency, region consisting of the islands, inadequate transportation, as well as teacher resources that have not mamadai and delays in salary for teachers in remote areas served.Keyword; The development of education, in the Kabupaten Natuna Post-Redistricting